2015
DOI: 10.1371/journal.pone.0136182
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Accelerated Right Prefrontal High-Frequency Repetitive Transcranial Magnetic Stimulation (rTMS) on Cue-Reactivity: An fMRI Study on Craving in Recently Detoxified Alcohol-Dependent Patients

Abstract: In alcohol-dependent patients craving is a difficult-to-treat phenomenon. It has been suggested that high-frequency (HF) repetitive transcranial magnetic stimulation (rTMS) may have beneficial effects. However, exactly how this application exerts its effect on the underlying craving neurocircuit is currently unclear. In an effort to induce alcohol craving and to maximize detection of HF-rTMS effects to cue-induced alcohol craving, patients were exposed to a block and event-related alcohol cue-reactivity paradi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 61 publications
2
37
0
Order By: Relevance
“…To date, nine studies have investigated the potential efficacy of rTMS in the treatment of alcohol use disorder, with mixed results. Six studies examined the effects of multiple sessions of rTMS (10–20 sessions) targeting the dorsolateral prefrontal cortex (DLPFC) or medial prefrontal cortex (mPFC), using a randomized, sham controlled study design. Findings from all six studies demonstrated a significant decrease in alcohol‐related cravings or consumption post‐active rTMS treatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, nine studies have investigated the potential efficacy of rTMS in the treatment of alcohol use disorder, with mixed results. Six studies examined the effects of multiple sessions of rTMS (10–20 sessions) targeting the dorsolateral prefrontal cortex (DLPFC) or medial prefrontal cortex (mPFC), using a randomized, sham controlled study design. Findings from all six studies demonstrated a significant decrease in alcohol‐related cravings or consumption post‐active rTMS treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Studies utilizing rTMS observed promising findings in trials conducted in nicotine or stimulant (cocaine, methamphetamine) dependent samples, with 10/11 and 5/7 positive studies, respectively in domains of craving and/or consumption. Moreover, in alcohol‐dependent participants, 6/9 studies suggested reductions in alcohol craving and/or consumption after active rTMS treatment. Effect sizes (Cohen's d) for rTMS on alcohol (−0.07–2.99), tobacco (−0.40–4.42), methamphetamine (−0.20–2.78), and cocaine (−1.82–3.58) were promising but highly variable, consistent with the (methodological) heterogeneity of the published studies (Table ).…”
Section: Discussionmentioning
confidence: 99%
“…The study was part of a larger project examining the neurobiological effects of HF‐rTMS on alcohol craving in alcohol‐dependent patients (during which the effect of 1 sham‐controlled and 15 accelerated HF‐rTMS sessions on alcohol craving and the corresponding craving neurocircuit is evaluated; published as Herremans et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…[1],(Mishra et al, 2016);[2],(Qiao et al, 2016);[3],(Jansen et al, 2015);[4],(Mishra et al, 2015);[5],(Mishra et al, 2010);[6],(Camprodon et al, 2007); [7], [8],(Herremans et al, 2016); [9],(Herremans et al, 2015);[10],(Herremans et al, 2013);[11],(Herremans et al, 2012);[12],(Wing et al, 2012);[13],(Dieler et al, 2014);[14],(Trojak et al, 2015);[15],(Liu et al, 2017);[16],(Klauss et al, 2018a); [17], (Shahbabaie et al, 2018a); [18], (Nakamura-Palacios et al, 2016); [19], (Wietschorke et al, 2016); [20],(Batista et al, 2015); [21], (Pripfl and Lamm, 2015); [22], (Conti et al, 2014); [23], (Conti and Nakamura-Palacios, 2014); [24], (Klauss et al, 2014); [25], (Gorini et al, 2014); [26], (Fecteau et al, 2014); [27], (Pripfl et al, 2013); [28], (Boggio et al, 2010); [29], (Boggio et al, 2008); [30], (Fregni et al, 2008); [31], (Shahbabaie et al, 2014); [32], (Mondino et al, 2018); [33], (Kamp et al, 2018); [34], (Liang et al, 2018a); [35], (Zhang et al, 2018); [36], (Li et al, 2017a); [37], (Li et al, 2017b); [38], (Sahlem et al, 2017); [39], (Su et al, 2017); [40], (Del Felice et al, 2016); [41], (Huang et al, 2016); [42], (Shen et al, 2016); [43], (Prikryl et al, 2014); [44], (Pripfl et al, 2014); [45],(Li et al, 2013a);[46],(Amiaz et al, 2009);[47],(Pettorruso et al, 2018);[48],(Terraneo et al, 2016);[49],(Politi et al, 2008);[50],(Sheffer et al, 2018); [51],(Hoppner et al, 2011);[52],(Eichhammer et al, 2003);[53],(Sheffer et al, 2013a;; [54], (Rapinesi et al, 2016); [55], (Li et al, 2013b); [56], (Baker et al, 2017); [57], (Yang et al, 2017); [58], (den Uyl et al, 2017); [59], (de Almeida Ramos et al, 2016); [60],…”
mentioning
confidence: 99%